20‐hydroxyecdysone enhances the expression of the chitinase 5 via Broad‐Complex Zinc‐Finger 4 during metamorphosis in silkworm, Bombyx mori. Issue 2 (29th December 2016) - Zhang, X.; Zheng, S.
Abstract: Insect chitinases are hydrolytic enzymes required for the degradation of chitin. They are essential for insect moulting and metamorphosis. In this study, the regulation mechanism of a chitinase gene, Bombyx mori chitinase 5 ( BmCHT5 ), was studied. Quantitative reverse transcription PCR (qRT‐PCR) analysis showed that BmCHT5 was up‐regulated during the larval–larval and larval–pupa transitions and notably induced by 20‐hydroxyecdysone (20E). Analysis of the BmCHT5 promoter revealed the presence of one Bombyx mori Broad‐Complex Zinc‐Finger Isoform 4 ( BR‐C Z4 ), two BR‐C Z2 and two ecdysone‐induced protein 74A ( E74A ) cis‐regulatory elements (CREs) that are related to 20E. qRT‐PCR showed that the expression of both BmBR‐C Z4 and BmBR‐C Z2 during metamorphosis, and when induced by 20E, was anastomotic with the variations in BmCHT5 mRNA level. In contrast, BmE74A did not follow this trend. An electrophoretic mobility shift assay did not retrieve a binding partner for the two BR‐C Z2 CREs in the Bm N cell line nuclear extract, whereas BR‐C Z4 CRE specifically bound to BmBR‐C Z4. Besides, luciferase activity analysis confirmed that BmBR‐C Z4 could enhance the activity of the BmCHT5 promoter with BR‐C Z4 CRE and could not enhance the promoter activity by mutating BR‐C Z4 CRE. Taken together, these data suggest that the transcription factor BmBR‐C Z4 enhances the expression of BmCHT5 during metamorphosis.